REDUKSI KLAUSA RELATIF RESTRIKTIF LENGKAP DALAM BAHASA INGGRIS DAN PADANANNYA DALAM BAHASA INDONESIA - Bambang Supriyanto (Jurnal Sosioteknologi, 2007)
Most full restrictive relative clauses in English can be reduced into reduced restrictive relative clauses, phrases, or words, but there are only few of them which cannot be reduced. Those are full restrictive relative clauses which have grammatical constructions as follows: (1) who/which + be + Noun, (2) Prep + who/which + Subject + Verb, (3) Who/which + Subject + Modal (except can/should), and (4) When/ where/why/ whose+ Subject/Verb